Evaluacija postkognitivističke kritike kompjutacijsko-reprezentacijskog shvaćanja uma: teorija dinamičkih sustava u kognitivnoj znanosti. - MUDRI, NEBOJŠA; VALERJEV, PAVLE (Prolegomena: Journal of Philosophy, 2026)
This article examines the relationship between the dynamical approach and the computational-representational models in cognitive science. The dynamical hypothesis is based on the understanding of cognition as a process that emerges from the coordination of brain, body and environment in real time, and relies on dynamical systems theory to explain self-organising patterns of behaviour. Unlike classical cognitivism and connectionism which explained cognitive processes algorithmically, either as the manipulation of discrete symbols through predefined rules or as the propagation of signals through neural networks according to parameter- modification algorithms that determine connection strengths, dynamical approaches emphasize continuous adaptation and interactivity within nonlinear and chaotic systems. Despite certain advantages of the dynamical approach in explaining complex and adaptive patterns of behaviour, it also faces numerous criticisms due to its potentially reductionist nature, particularly its neglect of higher levels of cognitive analysis, such as anticipation and planning, and its inaccuracy in describing intelligent behaviour. Complementary approaches attempt to reconcile these two perspectives by proposing that cognitive systems can be both embodied and symbolic, thereby explaining both flexible behaviour and more complex forms of cognition. In conclusion, post-cognitivist critical approaches should serve as an incentive for the removal of artificial boundaries between different disciplines and pave the way for the integration of dynamicism and computational-representational theory into a unified framework that allows for a more comprehensive understanding of cognition as a process that operates in both biological and social contexts.